2009
DOI: 10.1001/archoto.2009.1
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Chain Reaction for Pathogen Identification in Persistent Pediatric Cervical Lymphadenitis

Abstract: Objective: To study routine culture-negative persistent cervical lymphadenitis in children treated surgically during a 10-year period (December 26, 1997, to October 1, 2007) at a single institution.Design: Retrospective case series.Setting: Tertiary university-based pediatric referral center.Patients: Patients 18 years or younger with cervical lymphadenitis managed surgically (incision and drainage, curettage, and/or excisional lymphadenectomy) and medically (antibiotic therapy), culture-negative after 48 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…2 In those patients, the pain subsides within a few days whereas it takes several weeks to months for the lymphadenopathy to subside sonographically. Although cervicofacial lymphadenitis occurs frequently in children, a chronic persistent form can be a diagnostic and therapeutic challenge, 9 and CSD often remains unrecognized in cases of cervicofacial lymph node…”
Section: And the Most Common Anatomic Sites Ofmentioning
confidence: 99%
“…2 In those patients, the pain subsides within a few days whereas it takes several weeks to months for the lymphadenopathy to subside sonographically. Although cervicofacial lymphadenitis occurs frequently in children, a chronic persistent form can be a diagnostic and therapeutic challenge, 9 and CSD often remains unrecognized in cases of cervicofacial lymph node…”
Section: And the Most Common Anatomic Sites Ofmentioning
confidence: 99%
“…Many Filipinos who immigrated to the U.S. in the 1970's−1980's were nurses and Filipinos still constitute 75% of all foreign nurses in the U.S. nurse workforce ( 9 ). Previous exposure to ionized radiation has been shown to lead to higher percentages of multifocal disease, extrathyroidal spread, stage IV disease, and death in thyroid cancer, but multiple studies have suggested otherwise including studies on healthcare workers ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…If a pus sample is available, NTM aetiology can be confirmed by acid fast stain, culture and, recently, by polymerase chain reaction (PCR) [22,23]. So far, the proportion of infected lymph nodes with spontaneous recovery is unknown and, despite many reports available in literature have published about this item, the epidemiology and treatment of NTM lymphadenitis are still not well documented.…”
Section: Introductionmentioning
confidence: 99%